Implicações da utilização de diferentes números de progênies e repetições em um programa de seleção recorrente recíproca em milho - Baez, Olinda Estefania Ocampos (2017)
There is always concern about improving the strategies used in reciprocal recurrent selection (SRR) programs in maize. The number of progenies to be evaluated, as well as the number of replications used in the experiments are factors that will affect the gains in successive selection cycles. From the above, this work was carried out with the objective of obtaining, through computational simulation (Monte Carlo method), information about the best combination between the number of progenies evaluated and the number of replications, in order to optimize the expected progress in reciprocal recurrent selection programs that use full-sib progenies. A total of 163 progenies were evaluated in a RCB experiment with six replications. From the yield data of husked ears, different scenarios were simulated, involving 15 different numbers of evaluated progenies and 2, 4 and 6 replications. In each simulation, the phenotypic and genetic variances and heritability were estimated. Based on 5000 simulations, the amplitudes of variation (minimum and maximum) and standard errors were estimated. The results obtained in this study showed that the estimates vary which allows less in relation to their amplitudes, from a number of 100 progenies and when using 4 and 6 replications.